Combination of Thin-Layer Chromatography and Mass Spectrometry Using Cluster-Induced Desorption/Ionization - Heep, Julian (ACS Omega, 2019)
[Image: see text] Desorption/ionization induced by neutral clusters (DINeC) was employed for mass spectrometry (MS) of oligopeptides and lipids after separation by means of thin-layer chromatography (TLC). Clear and fragmentation-free spectra were obtained from the TLC plates without any further sample treatment. Mass-resolved chromatograms were deduced when scanning the TLC plates with the cluster beam along the direction of solvent movement. Using vancomycin and noncovalently bound complexes, the soft nature of DINeC was demonstrated also when used in combination with TLC. As a test application, TLC and DINeC–MS were employed to separate and detect different phospholipids obtained from egg yolk.